2007 IEEE Congress on Evolutionary Computation 2007
DOI: 10.1109/cec.2007.4424495
|View full text |Cite
|
Sign up to set email alerts
|

Evolvability and Redundancy in Shared Grammar Evolution

Abstract: Abstract-Shared grammar evolution (SGE) is a novel scheme for representing and evolving a population of variablelength programs as a shared set of grammatical productions. Productions that fail to contribute to selected solutions can be retained for several generations beyond their last use. The ensuing redundancy and its effects are assessed in this paper on two circuit design tasks associated with random number generation: finding a recurrent circuit with maximum period, and reproducing a De Bruijn counter f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This includes productions created for unfit solution candidates, so even a short delay leads to a substantial build-up. An earlier paper [41] provided an extensive study of this: most of the possible performance gain at the population size of 20 is observed for a single generation delay. We therefore also report on such a configuration for our problem tasks below.…”
Section: Promote Redundancymentioning
confidence: 94%
“…This includes productions created for unfit solution candidates, so even a short delay leads to a substantial build-up. An earlier paper [41] provided an extensive study of this: most of the possible performance gain at the population size of 20 is observed for a single generation delay. We therefore also report on such a configuration for our problem tasks below.…”
Section: Promote Redundancymentioning
confidence: 94%
“…The general approach of combining a grammar with an evolutionary algorithm leads to a developmental system (Luerssen and Powers 2007). Developmental systems, and more generally genetic programming methods (Riolo et al 2007), have been used widely for the design of electrical circuits (Koza et al 2008), a problem that shares some characteristics with the design of heat exchanger networks.…”
Section: Discussionmentioning
confidence: 99%